Pedogenic origin of precious opals from Wegel Tena (Ethiopia): Evidence from trace elements and oxygen isotopes. (February 2019) - Chauviré, Boris; Rondeau, Benjamin; Alexandre, Anne; Chamard-Bois, Sarah; La, Carole; Mazzero, Francesco
Abstract: The trace element and oxygen isotope composition of Wegel Tena (Ethiopia) gem opals was measured to provide evidence of the conditions of their genesis. Elemental measurements display several behaviors, especially for K, Ca, Sr and Ba suggesting that—in agreement with previous assumptions—the silica-rich fluids that precipitate into opal are fed by the weathering of ignimbrite at several degrees. The distribution of elements in the opals indicates that the sources of silica in the ignimbrite are both glass and feldspar. Rare Earth Element (REE) signatures are also consistent with a weathering process, but underline that a wide range of physical and chemical conditions prevail at the regional, local and even intra-sample scales. The Ce anomaly emphasizes the variations in redox conditions during opal precipitation, whereas Eu anomaly indicates that feldspar dissolution feeds some of the silica-rich fluids. This suggests that the fluid responsible for opal precipitation is not homogenous across the area with underground water circulation, but rather that each sample reflects formation conditions specific to its very local environment. The oxygen isotope signatures of the opals (from 26.52 to 30.98‰ vs SMOW) allow us to formulate several hypotheses concerning their temperature of formation and the isotopic composition of the fluid. The hypothesis consistent with our other measurements is the pedogenic formation of the opals at ambient temperature (18–21 °C) involving a slightly evaporated soil water fed by meteoric water with an isotopic composition lower than at present, during an Oligocene period likely warmer and wetter than today. Highlights: Minor and trace elements is used to trace the source of silica of opal precipitation. REE is a tool to understand the physical and chemical conditions of opal genesis. Oxygen isotope demonstrate that opal precipitates from water in Oligocene soil. Wegel Tena opal precipitates from water in soil, at 18–21 °C.